A Study of Etiological Spectrum of Maternal Near-miss Cases and Quality Care Indicators in Western Region of India - Alhad A. Pande; Zalak Vinaybhai Karena; Kamal D. Goswami (NMO Journal)
Background: Maternal death review has remained the fundamental quality care indicator for any maternal health-care governance program. Maternal near-miss (MNM) cases which are the forerunner of mortality cases could serve as a proxy indicator to evaluate the obstetric quality care. Objectives: To calculate MNM to mortality ratio of the institute and to study the etiological spectrum of MNM cases. Materials and Methods: A hospital-based prospective observational study was carried out. Cases were taken as defined based on the WHO MNM criteria. Data collection was done through information retrieval from case records and by in-depth interviews with the help of semi-structured questionnaire of MNM cases from 2 days after their admission up till discharge. Each case was documented with respect to the demographic details, adverse events and aetiology. Results: The MNM to mortality ratio was 1.16:1, MNM incidence ratio in our study was 4.12 and the mortality index was 46.23. Seventy-six per cent of cases were referred cases. The main causes for near-miss were post-partum haemorrhage (30%) followed by pre-eclampsia (26%). Hypertension was the most significant comorbidity in 28% of cases, while 26% had cardiac disease and 26% had severe anaemia. Conclusions: Studying near-miss mortality cases provides a valuable insight of the quality of care of the institute. MNM case review should be a part of regular governance process of the maternity care unit to plan and implement focused care.